Effects of protein kinase a phosphorylation on the biochemical properties and subcellular location of human choline kinase beta - Cun, See Too Wei (Pusat Pengajian Kesihatan, 2016)
Choline kinase is the most upstream enzyme in the CDP-choline pathway. It catalyzes the phosphorylation of choline to phosphorylcholine in the presence of ATP and Mg2+ during the biosynthesis of phosphatidylcholine, the major phospholipid in eukaryotic cell membranes. In humans, choline kinase (CK) is encoded by two separate genes, cka and ckp, which produce three isoforms, CKa1, CKa2, and CKp. Previous studies have associated ckp with muscle development; however, the molecular mechanism underlying the transcriptional regulation of ckp has never been elucidated. In this report, the distal promoter region of the ckp gene was characterized. Mutational analysis of the promoter sequence and electrophoretic mobility shift assays (EMSA) showed that Ets and GATA transcription factors were essential for the repression of ckp promoter activity. Supershift and chromatin immunoprecipitation (ChIP) assays further identified that GATA3 but not GATA2 was bound to the GATA site of ckp promoter. In addition, phorbol-12-myristate-13-acetate (PMA) decreased ckp promoter activity through Ets and GATA elements. PMA also decreased the ckp mRNA and protein levels about 12 hours after the promoter activity was down-regulated. EMSA further revealed that PMA treatment increased the binding of both Ets and GATA transcription factors to their respective DNA elements. The PMA-mediated repressive effect was abolished by chronic PMA treatment and by treatment with the PKC inhibitor PKC412, but not the PKC inhibitor Go 6983, suggesting PKCe or PKCq as the PKC isozyme involved in the PMA-mediated repression of ckp promoter. Further confirmation by using PKC isozyme specific inhibitors identified PKCe as the isozyme that mediated the PMA repression of ckp promoter.